The lives of the novel a history - Pavel, Thomas G. 1941- (Princeton, New Jersey Princeton University Press, 2013)
This is a boldly original history of the novel from ancient Greece to the vibrant world of contemporary fiction. Thomas Pavel argues that the driving force behind the novel's evolution has been a rivalry between stories that idealize human behavior and those that ridicule and condemn it. Impelled by this conflict, the novel moved from depicting strong souls to sensitive hearts and, finally, to enigmatic psyches. Pavel makes his case by analyzing more than a hundred novels from Europe, North and South America, Asia, and beyond. The result is a wide-ranging survey of the novel and a provocative reinterpretation of its development. -- Publisher website.
Strong souls, degrees of perfection -- Helpless souls, tricksters, and rascalsod -- The center of action: elegiac stories and novellas -- An isolated realm, hesitant lovers: the pastoral -- Don Quixote and the history of the novel -- The new idealism -- Resistance to new idealism -- Love: romantic and impossible -- Novels and society -- From sensitive hearts to enigmatic psyches -- Syntheses, high points -- Loners in a strange world.
"First published in France as La Pense du roman©Editions Gallimard, Paris, 2003."--Title page verso.
Includes bibliographical references (pages 301-317) and index.
Keywords: Fiction -- History and criticism